2002
DOI: 10.1590/s1415-52732002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Anemia prevalence in children and adolescents from educational centers in the outskirts of Londrina, PR, Brazil

Abstract: Iron deficiency anemia is the world most prevalent nutritional problem. To investigate anemia prevalence and its relation to nutritional status, 526 children and adolescents, 284 males and 242 females, aged 7 to 14 years old, were evaluated. The studied subjects take part in a program of the Social Action Department of the city of Londrina, state of Paraná, and attend Public Educational Centers which provides them three daily meals and pedagogic assistance. These individuals belong to deprived areas in the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
1
1
0
4
Order By: Relevance
“…13 Santos et al 14 conducted a study with students (6–10 years) of public schools in Maceió and found a 9.9% prevalence of anemia. Another study conducted by Miglioranza et al 15 in the same region as this present work found a 41.3% prevalence of anemia in children and adolescents ( n = 526) aged 7–14 years using Hb <12.0 g/dL as the main criterion. In Brazil, there is no national survey on the prevalence of anemia, only regional studies, which report variable prevalences of anemia depending on the region and socioeconomic conditions of the analyzed population.…”
Section: Discussionsupporting
confidence: 66%
“…13 Santos et al 14 conducted a study with students (6–10 years) of public schools in Maceió and found a 9.9% prevalence of anemia. Another study conducted by Miglioranza et al 15 in the same region as this present work found a 41.3% prevalence of anemia in children and adolescents ( n = 526) aged 7–14 years using Hb <12.0 g/dL as the main criterion. In Brazil, there is no national survey on the prevalence of anemia, only regional studies, which report variable prevalences of anemia depending on the region and socioeconomic conditions of the analyzed population.…”
Section: Discussionsupporting
confidence: 66%
“…O aumento da necessidade de nutrientes durante a adolescência, aliado a características como a crescente independên-cia, alterações psicológicas, busca de autonomia, definição da própria identidade, influência de amigos, demandas escolares e de trabalho, pressões e modificação das preferências alimentares e rebeldia contra padrões familiares, pode colocar este grupo em risco nutricional 11 . Além disso, apesar de diversos estudos populacionais detectarem a prevalência de anemia em escolares e adolescentes [12][13][14][15][16][17][18] , poucos relacionam a anemia por deficiên-cia de ferro à maturidade sexual dos indivíduos 17,18 . Foi formulada a hipótese de que o crescimento da adolescência poderia interferir na prevalência de anemia e nos níveis séricos de hemoglobina nos sexos masculino e feminino.…”
Section: Introductionunclassified
“…Vitalle e Fisberg 20 explicam que na adolescência os sintomas da anemia são sutis, passando muitas vezes despercebidos, porém alguns sinais são marcantes como a fadiga, fraqueza e emagrecimento. Nesse mesmo sentido Almeida 21 especifica que, embora de forma quase imperceptível, a deficiência de ferro apresenta quadro clínico de "palidez cutâneo-mucosa, astenia, fadiga, distúrbio alimentar e redução do crescimento", sendo que o principal comprometimento está na diminuição do transporte de oxigênio para os tecidos devido a diminuição da concentração de hemoglobina.…”
Section: Discussionunclassified